Non-homogeneous Fabry-Pérot Antenna Design at Ku-band - Mateos-Ruiz, Pablo; Abdo-Sánchez, María Elena; Camacho-Peñalosa, Carlos (My University, 2021)
A novel technique to design Fabry-Pérot antennas with non-homogeneous PRS is described. It takes advantage of a transmission line circuit model to efficiently obtain all necessary unit cell designs that satisfy the cavity resonance condition. This approach allows an increase in directivity for a given footprint without decreasing the bandwidth. Some design examples are presented, showing the evolution from a simple single-layer PRS to a non-homogeneous two-layers one. Through electromagnetic simulations, the latter one achieves an increase of about 3 dB in directivity while maintaining the bandwidth. This way, the gain-bandwidth product is improved from a value of 5 to almost 9, effectively raising the antenna efficiency.
Keywords: Antenas; Redes de banda ancha; Fabry-Pérot Antenna; Partially Reflective Surface; Circuit modelling; Wideband; Non-homogeneous